Game Geometri Digital (Gaged) untuk Pengembangan Kemampuan Kognitif pada Anak Usia 3-4 Tahun - Susanti, Brigita Ika; Wijaya, Intan Prastihastari; Khan, Rosa Imani (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2022)
The development of cognitive capacities in early childhood to introduce geometry through digital geometry games seeks to enable children to recognize the shapes of items around them. Geometry games can also help children learn to solve problems on their own. The difficulty in pairing geometric images that match their companion was identified as an issue in the Play Group Santo Yoseph II Kediri for children aged 3-4 years. Researchers are introducing computer games to 5 children aged 3 to 4 years as part of an effort to solve this problem. The study's findings are deemed successful because the results of the assessment of measuring activities through digital geometry game media for students aged 8 to 12 years old were obtained from the calculations in the second cycle.